Effects of stocking density and climate region on performance, immunity, carcass characteristics, blood constitutes, and economical parameters of broiler chickens - Gholami, Majid; Chamani, Mohammad; Seidavi, Alireza; Sadeghi, Ali Asghar; Aminafschar, Mehdi (Brazilian Journal of Animal Science, 2020)
This experiment was conducted to evaluate the effects of stocking density and climate region on performance, immunity, carcass characteristics, blood plasma, and economic parameters of the Ross strain of broiler chickens. The effects of four climates (mild and humid, semi-arid, alpine, and hot and dry) and four densities (10, 15, 17, and 20 chicks/m2 ) were studied as a completely randomized design with 4×4 factorial arrangement of treatments. The results showed that the density had a significant effect on feed intake and feed conversion ratio in the starter period and on body weight gain in the grower and the whole periods of the experiment. Moreover, both climate and density had a significant impact on economic performance (live weight, survival rate, production index, meat production/m2 , and profitability). The mild and humid climate and the density of 17 chicks/m2 had the most economic benefit compared with other treatments. The climate type had a significant effect on the relative weights of the breast, wings, neck, proventriculus, and ileum. The effects of climate and density on glucose, triglyceride, very low-density lipoproteins (VLDL), high-density lipoproteins (HDL), LDL/low-density lipoproteins (HDL), total protein and globulin were significant. In addition, the effect of climate on the antibody titer against sheep red blood cells (except for immunoglobulin G on day 28) was significant
Keywords: blood plasma; chick; climate; density; feed conversion ratio; immunity